2012
DOI: 10.1017/s000711451200150x
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 polyunsaturated fatty acids and body weight

Abstract: In animal studies, n-3 PUFA have been shown to influence body composition and to reduce the accumulation of body fat, thereby affecting body weight homeostasis. In addition, it has been suggested that an additional supply of n-3 PUFA during pregnancy or lactation, or both, would have a beneficial effect on birth weight and infant growth and development. The purpose of the present study was to systematically review interventional clinical trials on the effects of dietary n-3 PUFA supplementation on body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 39 publications
0
29
0
3
Order By: Relevance
“…Previous reports have indicated that dietary GTE and FO can reduce body weight by increasing fat oxidation (Rains et al, 2011;Martínez-Victoria and Yago, 2012;Buckley and Howe, 2010;Sae-Tan et al, 2011). Previously, we showed that FO intake also reduced Hg accumulation in muscle and led to loss of body weight in MeHg-exposed mice (Shirai et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports have indicated that dietary GTE and FO can reduce body weight by increasing fat oxidation (Rains et al, 2011;Martínez-Victoria and Yago, 2012;Buckley and Howe, 2010;Sae-Tan et al, 2011). Previously, we showed that FO intake also reduced Hg accumulation in muscle and led to loss of body weight in MeHg-exposed mice (Shirai et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…In a controlled 16-week study in overweight and moderately obese healthy adults, increasing the dietary content of n-3 PUFA to 3.6%E mainly from fish oil had no effect on body weight or fat mass [56]. A recent review reached a similar conclusion [57]. Thus, fish or n-3 PUFA intakes may have little effect on body weight or weight gain.…”
Section: Fat Quality In Obesity and Insulin Resistancementioning
confidence: 99%
“…Seven of the included publications on maternal long-chain polyunsaturated fatty acid (LC-PUFA) supplementation were systematic reviews (Muhlhausler et al, 2010;Campoy et al, 2012;Rodriguez et al, 2012;Martinez-Victoria and Yago, 2012;Koletzko et al, 2014b;Stratakis et al, 2014;DelgadoNoguera et al, 2015), one of which a Cochrane review (Delgado-Noguera et al, 2015). The remaining 3 documents were original reports of randomized controlled trials (RCTs) (Jensen et al, 2010;Bergmann et al, 2012;Hauner et al, 2012) (Table 3).…”
Section: Long-chain Polyunsaturated Fatty Acid Supplementation Duringmentioning
confidence: 99%